Canine leishmaniasis control in the context of one health - Dantas-Torres, Filipe; Miró, Guadalupe; Baneth, Gad; Bourdeau, Patrick; Breitschwerdt, Edward; Capelli, Gioia; Cardoso, Luís; Day, Michael J.; Dobler, Gerhard; Ferrer, Luis; Irwin, Peter; Jongejan, Frans; et al. (Centers for Disease Control and Prevention (CDC), 2019)
Dogs are the main reservoir of Leishmania infantum and in some countries have been regularly culled as part of government policy to control visceral leishmaniasis. At the 13th Symposium of the Companion Vector-Borne Diseases World Forum in Windsor, UK, March 19-22, 2018, we consolidated a consensus statement regarding the usefulness of dog culling as a means of controlling visceral leishmaniasis. The statement highlighted the futility of culling infected dogs, whether healthy or sick, as a measure to control the domestic reservoir of L. infantum and reduce the risk for visceral leishmaniasis.